Challenges and Pedagogical Strategies in Implementing Translanguaging Among Indonesian EFL Teachers: A Case Study - Laksono, Kukuh Tri; Sumardi, Sumardi; Putra , Kristian Adi (Universitas Pendidikan Mandalika, 2025)
This study investigates the challenges and strategies faced by Indonesian EFL teachers in implementing translanguaging pedagogy in their classrooms. Translanguaging, which involves using multiple languages in the learning process, offers both opportunities and difficulties in multilingual contexts.The purpose of the study is to explore EFL teachers’ challanges and how they manage translanguaging in the classroom. A qualitative case study was used in order to explain the used of translanguaging. The study conducted with three junior high school EFL teachers, the research employed classroom observations and semi-structured interviews. The findings revealed several challenges, including students' over-reliance on their native languages, lack of clear translanguaging policies, and insufficient exposure to English, which hindered language development. Teachers faced difficulty in balancing English use and students’ reliance on their daily languages, with some struggling to establish consistent rules for translanguaging. To address these issues, teachers implemented strategies such as setting clear classroom rules, encouraging English practice outside the classroom, and gradually increasing English exposure in lessons. However, the study highlighted the lack of clear strategies and support from institutional policies, making it difficult for teachers to effectively manage translanguaging. It can be implied that without clear institutional policies and targeted teacher training, the potential benefits of translanguaging in EFL classrooms may not be fully realized, as teachers struggle to balance English exposure with students’ use of their native languages.